PENGARUH DIFERENSIASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN (STUDI PADA ROSEBERRY CAKE SHOP GARUT) - Suca Rusdian (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
This research is motivated by the purchase decision at Roseberry Cake Shop Garut which is not optimal. One thing that can be done to improve purchasing decisions is through an appropriate product differentiation strategy. The purpose of this study was to determine the effect of product differentiation on purchasing decisions at Roseberry Cake Shop Garut. The methodology used is descriptive method with associative problem formulation. The data analysis technique used the validity instrument, the reliability instrument test, the Spearman rank correlation coefficient test, the determination coefficient test and hypothesis testing using SPSS Version 20 and the formula. Based on the results of testing and statistical analysis using the Spearman rank correlation test, there is a "very strong" influence between the variables of product differentiation and purchasing decisions. This is indicated by the spearman rank correlation value of 0.813. While the magnitude of the contribution of the influence of the product differentiation variable on purchasing decisions using the coefficient of determination obtained the results of 66.1% and the remaining 33.9% is influenced by other factors that are not discussed in this study. Then based on the hypothesis test, it is known that the t-count value is 11,343, which means the t-count value is 11,343> t-table 1.670 and the sig value 0.000 <0.05, so it can be concluded that Ho is rejected and Ha accept which means Product Differentiation has a positive and significant effect on Purchasing Decisions. in Roseberry. Keywords: Product Differentiation, Purchasing Decision